Longitudinal Variations in Physiochemical Conditions and Their Consequent Effect on Phytoplankton Functional Diversity Within a Subtropical System of Cascade Reservoirs - Shen, Henglun; Ye, Lin; Cai, Qinghua; Tan, Lu (Frontiers in Ecology and Evolution, 2022)
The social and environmental impacts of large dams are quantifiable and have been well documented, while small dams have often been presumed to be less environmentally damaging than large dams. The purpose of this study was to analyze longitudinal gradients in environmental, hydrodynamic variables and its impact on phytoplankton function, within a cascade of four reservoirs (XuanMiaoGuan, XMG; TianFuMiao, TFM; XiBeiKou, XBK; ShangJiaHe, SJH) and one reservoir-bay (Huangbohe Bay, HBH), located from upstream to downstream in the Huangbo River, in Hubei Province of China. Our results showed that water temperature, total nitrogen and soluble silicate increased along the cascade reservoir system, while the concentration of dissolved oxygen and total phosphorus decreased. We identified 16 phytoplankton functional groups were identified, and the predominant groups including D (Synedra and Stephanodiscus hantzschii), E (Dinobryon divergens), Lo (Dinoflagellate: Peridinium bipes and Peridiniopsis), X2 (Chroomona) and Y (Cryptomonas), changed longitudinally from up to down in the cascade reservoirs. The number of dominant functional groups increased along the longitudinal gradient, indicating that the function of the phytoplankton community was more stable. Functional group D was the dominant phytoplankton functional group among the four reservoirs, and Lo group was dominant except SJH. The phytoplankton functional groups in the HBH have been completely changed due to the backwater jacking of the main stream of the Yangtze River. Euphotic depth, suspended solids and nutrients were apparently the key factors driving variations in phytoplankton functional groups among the reservoirs. Notably, the patterns we observed were not all consistent with the Cascading Reservoir Continuum Concept (CRCC) that typically characterizes on large rivers. Thus, our findings contribute to the further theoretical development of the CRCC, which may not apply widely to all cascade systems.